The demography of the Egyptian Goose, its impacts on cereal crop agriculture on the Agulhas Plain, Western Cape, South Africa and the measures to mitigate damage to crops by geese - Mangnall, Michael John (Department of Biological Sciences, 2015)
Bibliography: leaves 93-102.